Phenomenological Research On Guest Couchsurfing Experience - Karakan, Halil İbrahim; Birdir, Kemal; Akin, Aliye; Akin, Adnan (Turyzm/Tourism, 2021)
Couchsurfing (CS) is now regarded as an alternative platform that reflects changes in tourist accommodation preferences. The CS platform, based on the sharing economy, offers an opportunity to give various tourist experiences to travelers, as well as accommodation. This study aims to provide information about the travel motivations, prejudices, risk perceptions and experiences of CS guests. It has original value for the relevant literature, as it delves deeply into CS guests using a phenomenological approach. The present results show that the desire to sightsee new places, meet new people and recognize different cultures has motivated the participants. The study found that although most of the participants did not have prejudices or risk perceptions, CS first timers did. It has also been observed that participants are highly satisfied with their CS experiences and intend to take part in CS activities again.